Higher maternal plasma folate but not vitamin B-12 concentrations during pregnancy are associated with better cognitive function scores in 9-10 year old children in South-India(-) - Veena, Sargoor R (2010)
Folate and vitamin B-12 (B-12) are essential for normal brain development. Few studies have examined the relationship of maternal folate and B-12 status during pregnancy to offspring cognitive function. To test the hypothesis that lower maternal plasma folate and B-12 concentrations and higher plasma homocysteine concentrations during pregnancy, are associated with poorer neurodevelopment, cognitive function was assessed during 2007-2008 among 536 children (aged 9-10 y) from the Mysore Parthenon birth cohort. Maternal folate, B-12 and homocysteine concentrations were measured in stored plasma samples taken at 30±2 wk gestation. The children’s cognitive function was measured using 3 core tests from the Kaufman Assessment Battery and additional tests measuring learning ability, long-term storage/retrieval, attention and concentration, visuo-spatial and verbal abilities. During pregnancy 4% of mothers had low folate concentrations (<7 nmol/L), 42.5% had low B-12 concentrations (<150 pmol/L) and 3% had hyperhomocysteinemia (>10 μmol/L). There was a 0.1-0.2 SD increase in the children’s cognitive scores per SD increase in maternal folate concentration (p<0.001 for all tests). The associations with learning ability and long-term storage/retrieval, visuo-spatial ability, attention and concentration were independent of maternal age, BMI, parity, the parents’ education, socio-economic status, rural/urban residence, religion, the child’s gestational age, birth size, sex and the children’s size, educational level and folate and B-12 concentrations at 9.5 y. There were no consistent associations of maternal B-12 and homocysteine concentrations with childhood cognitive performance. CONCLUSIONS: In this Indian population higher maternal folate, but not vitamin B-12 concentrations during pregnancy, predicted better childhood cognitive ability.